2018
DOI: 10.1186/s40168-018-0526-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbiomes with distinct assemblies through vertical soil profiles drive the cycling of multiple nutrients in reforested ecosystems

Abstract: BackgroundSoil microbiomes play an important role in the services and functioning of terrestrial ecosystems. However, little is known of their vertical responses to restoration process and their contributions to soil nutrient cycling in the subsurface profiles. Here, we investigated the community assembly of soil bacteria, archaea, and fungi along vertical (i.e., soil depths of 0–300 cm) and horizontal (i.e., distance from trees of 30–90 cm) profiles in a chronosequence of reforestation sites that represent ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
270
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(303 citation statements)
references
References 76 publications
28
270
5
Order By: Relevance
“…The impacts of natural and artificial revegetation of abandoned farmland on the ecological environment have been intensively examined, contributing to adjustments in land‐use policy and combinatorial optimization in ecological restoration strategies worldwide (Barber, Chantos‐Davidson, Amel Peralta, Sherwood, & Swingley, ; Jiao et al, ; Lozano, Hortal, Armas, & Pugnaire, ; Nadal‐Romero, Cammeraat, Pérez‐Cardiel, & Lasanta, ). Abandoned farmland can sustain secondary succession (passive restoration) or afforestation (active restoration), leading to a mosaic of reconstructed vegetation and artificial forests (Nadal‐Romero et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of natural and artificial revegetation of abandoned farmland on the ecological environment have been intensively examined, contributing to adjustments in land‐use policy and combinatorial optimization in ecological restoration strategies worldwide (Barber, Chantos‐Davidson, Amel Peralta, Sherwood, & Swingley, ; Jiao et al, ; Lozano, Hortal, Armas, & Pugnaire, ; Nadal‐Romero, Cammeraat, Pérez‐Cardiel, & Lasanta, ). Abandoned farmland can sustain secondary succession (passive restoration) or afforestation (active restoration), leading to a mosaic of reconstructed vegetation and artificial forests (Nadal‐Romero et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies found that arable soils were similar or more diverse than the original ecosystem and that functional redundancy overcomes the ecosystem transformation. Most studies, however, have determined Shannon and Simpson indices and they did not report on the magnitude of the changes (Mendes et al, 2015;Castañeda and Barbosa, 2017;Goss-Souza et al, 2017;Jiao et al, 2018). However, the effect on soil biodiversity of conversion of high-altitude temperate forest to arable land has not yet been investigated and as the vegetation and environmental conditions are different, it is difficult to predict what the effect might be.…”
Section: Discussionmentioning
confidence: 99%
“…The percentages of overlap and turnover of species or functions were determined through the multiplicative partition of beta-diversity. The alpha diversity profile at q = 0, 1, 2, 3 and 4 of soil communities, and the overlap and turnover rate at q = 0, 1 and 2 between communities were obtained with Meta-genomeDiversity script in R (Ma and Li, 2018). The percentages of diversity shared between soils were calculated as described by Moreno et al (2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The soil ecosystem is particularly important for agriculture since it contributes to the decomposition of organic matter and litter, which plays a major role in resource recycling, 10 nutrient retention and uptake by the plant, water regulation and biogeochemical cycling. 11,12 All these processes together potentially enrich the soil with mineral nutrients and redistribute the organic matter that comes from plant residues, 13 increasing soil health and www.soci.org A Guerrieri, L Dong, HJ Bouwmeester fertility and thus improving crop yield. In addition, soil organisms influence many aspects of the plant, from belowground to aboveground.…”
Section: The Soil Ecosystem and Its Importance For Agriculturementioning
confidence: 99%